Kesesuaian Lahan Sawah Dilindungi Terhadap Rencana Tata Ruang Wilayah di Kecamatan Tanah Sepenggal Kabupaten Bungo - Arisma Wardhani, Adinda; Arco Gumilar, Binar; Rahmanisful Laili, Difa; Fadly Raharjo, Rasyid; Purna Hadi, Rasyid (Sekolah Tinggi Pertanahan Nasional, 2025)
Indonesia's food security faces serious challenges due to declining rice productivity and massive conversion of rice fields. The Protected Rice Fields (Lahan Sawah Dilindungi/LSD) policy under Presidential Regulation No. 59/2019 was designed to address this issue, yet its implementation often lacks synchronization with Regional Spatial Plans (Rencana Tata Ruang Wilayah/RTRW). Tanah Sepenggal Sub-district, Bungo Regency, serves as a critical case study due to its role as a rice production center in Jambi Province that is experiencing pressure from land conversion to oil palm plantations. This study aims to: (1) identify spatial discrepancies between LSD and RTRW, (2) analyze differences between actual land use and RTRW designations, and (3) evaluate government efforts to address these mismatches. The research employs a descriptive qualitative method with spatial analysis using GIS overlay techniques of LSD maps, RTRW, and land use maps. Data were obtained from the Bungo Regency Land Office and Agricultural Office. Findings reveal that 76.49% of LSD areas (497.55 Ha) in Tanah Sepenggal align with RTRW as agricultural zones, while 23.51% (152.95 Ha) show inconsistencies, being designated for urban development (21.83%) and river buffer zones (1.69%). Land use analysis indicates only 33.7% of LSD areas remain functional as rice fields, with 66.3% converted to plantations (56.29%) and settlements (1.86%). The LSD-RTRW discrepancies in Tanah Sepenggal stem from weak inter-agency coordination, competing economic interests, and insufficient farmer incentives. Policy recommendations include: (1) RTRW revision based on updated spatial data, (2) economic incentives through Transfer of Development Rights (TDR) schemes, and (3) strengthened monitoring of land conversion. This study emphasizes the necessity of integrating spatial planning policies with sustainable agricultural land protection. Keywords: Protected Rice Fields, Regional Spatial Planning, Land Use Conversion, Tanah Sepenggal, Food Security INTISARI Ketahanan pangan Indonesia menghadapi tantangan serius akibat penurunan produktivitas padi dan alih fungsi lahan sawah yang masif. Kebijakan Lahan Sawah Dilindungi (LSD) melalui Perpres No. 59/2019 dirancang untuk mengatasi masalah ini, namun implementasinya sering tidak sinkron dengan Rencana Tata Ruang Wilayah (RTRW). Kecamatan Tanah Sepenggal, Kabupaten Bungo, menjadi studi kasus kritis karena kontribusinya sebagai sentra padi di Provinsi Jambi yang mengalami tekanan alih fungsi lahan ke perkebunan kelapa sawit. Penelitian ini bertujuan untuk: (1) mengidentifikasi ketidaksesuaian spasial antara LSD dan RTRW, (2) menganalisis perbedaan penggunaan lahan aktual dengan arahan RTRW, dan (3) mengevaluasi upaya pemerintah dalam mengatasi ketidaksesuaian tersebut. Penelitian menggunakan pendekatan kualitatif deskriptif dengan analisis spasial berbasis overlay peta LSD, RTRW, dan penggunaan tanah di ArcGIS. Data diperoleh dari Kantor Pertanahan Kabupaten Bungo dan Dinas Pertanian. Temuan menunjukkan bahwa 76,49% LSD (497,55 Ha) di Kecamatan Tanah Sepenggal sesuai dengan RTRW sebagai kawasan pertanian, sementara 23,51% (152,95 Ha) tidak sesuai karena termasuk dalam arahan perkotaan (21,83%) dan sempadan sungai (1,69%). Analisis penggunaan tanah mengungkapkan hanya 33,7% LSD yang masih berfungsi sebagai sawah, sedangkan 66,3% telah beralih fungsi menjadi perkebunan (56,29%) dan permukiman (1,86%). Ketidaksesuaian LSD-RTRW di Tanah Sepenggal disebabkan oleh lemahnya koordinasi antarinstansi, dinamika kepentingan ekonomi, dan kurangnya insentif bagi petani. Rekomendasi kebijakan meliputi: (1) revisi RTRW berbasis data spasial terbaru, (2) pemberian insentif ekonomi melalui skema TDR (Transfer Development Right), dan (3) penguatan pengawasan alih fungsi lahan. Studi ini menegaskan perlunya integrasi kebijakan tata ruang dengan perlindungan lahan pertanian berkelanjutan. Kata Kunci: Lahan Sawah Dilindungi, Rencana Tata Ruang Wilayah, Alih Fungsi Lahan, Tanah Sepenggal, Ketahanan Pangan